Effects of Apply Local Dance Program on Physical Fitness and Quality of Life in Older Persons in Na Yia Sub-District, Na Yia District, Ubonratchathani Province - Sooktho, Suparat; Sangprapai, Warinee; Junlatat, Jintana; Nusawat, Suphannachat; kamuttachat, Phanida (Princess of Naradhiwas University Journal, 2022)
When entering old age, there is a degenerative of both the psychological and physical systems such as the musculoskeletal system. Moreover, the function of the nervous system decreases and affects the loss of balance. This one group pretest-posttest design aimed to examine the effects of applied local dance program on physical fitness and quality of life. The participants were 17 older adults living in village 2, Na Yia sub-district, Na Yia district Ubonratchathani province, received the applied local dance program for 40 minutes per day, three days a week for consecutive 12 weeks. The participants were measured pre-posttest on cardiac and vascular endurance, leg muscle strength, around the shoulder, lower back and posterior thigh muscle flexibility, dynamic and static balance, and quality of life. This study found that the leg muscle strength test, around the shoulder, lower back, and posterior thigh muscle flexibility, the dynamic and static balance test, and quality of life were statistically significant improvements (p<0.05). This study indicates that the 15 postures in the applied local dance program can improve physical fitness and quality of life in older persons.